Pengaruh Konsentrasi Ekstrak Daun Salam (Syzygium polyanthum) Pada Marinasi Daging Bebek Terhadap Daya Ikat Air, Susut Masak, Keempukan dan Organoleptik - Novalina, Icah; Suryaningsih, Lilis; Gumilar, Jajang (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Duck meat has a lower physical quality because the texture of the meat is tough and smells fishy, a method that can improve the quality of duck meat is needed. One of the meat preservation methods is marination using natural ingredients such as bay leaves. This study aims to determine the effect and best concentration of bay leaf extract (Syzygium polyanthum) on water binding capacity, cooking shrinkage, tenderness and organoleptic of duck meat. This study used a completely randomized design with 5 treatments of extract concentration (P0=0%, P1=5%, P2=10%, P3=15% and P4=20%) and 4 replications. If the treatment is significantly different, it is continued with the Duncan multiple range test. Organoleptic parameters, using Kruskal-Wallis non-parametric statistical test with Mann-Whitney further test. The results showed that marination using bay leaf extract had a significant effect on tenderness and organoleptic values, but had no significant effect on water binding capacity and cooking shrinkage. The use of bay leaf extract with 10% concentration produced the best marination with DIA 46.33%, cooking shrinkage 36.67%, tenderness 2.34kgf and organoleptic color 3.75 (like), aroma 4.00 (like), flavor 3.80 (like) and total acceptance 4.15 (suka).